Keputusan Pembelian Emina Solo Raya: Pengaruh E-Wom, Promosi dan Brand Image - Silvia Putri Riswardani; Esti Dwi Rahmawati; Agus Suyatno (Jurnal Publikasi Ilmu Manajemen, 2024)
This research aims to analyze the mediating role of consumer trust in the influence of electronic word of mouth and promotions on purchasing decisions with brand image as an intervening variable for Emina products in Solo Raya. The population in this study were Emina product users in Solo Raya and the total sample in the Ink research was 96 respondents. The variables used in this research are electronic word of mouth, promotions, purchasing decisions and brand image. The data used in this research is primary data. The data collection method used was a questionnaire. The data analysis technique used is Structual Equation Modeling-apartial Least Square (SEM-PLS) and uses the SmartPLS 4.0 program. The results of this research show that brand image has a positive and significant effect on purchasing decisions, electronic word of mouth has a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on purchasing decisions, promotion has a positive and significant effect on brand image, promotions have a positive and significant effect on purchasing decisions, brand image is able to mediate the influence of electronic word of mouth on purchasing decisions, brand image is not able to mediate the influence of promotions on purchasing decisions.